2019
DOI: 10.3390/coatings9050302
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Gallic Acid onto a Bioactive Ti6Al4V Alloy: A Physico-Chemical Characterization

Abstract: Despite increasing interest in the use of natural biomolecules for different applications, few attempts of coupling them to inorganic biomaterials are reported in literature. Functionalization of metal implants with natural biomolecules could allow a local action, overcoming the issue of low bioavailability through systemic administration. In the present work, gallic acid was grafted to a pre-treated Ti6Al4V in order to improve its biological response in bone contact applications. The grafting procedure was op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 62 publications
3
24
0
3
Order By: Relevance
“…Polyphenols decrease inflammatory mediators, such as histamine, and cytokines. Consequently decrease bone resorption 29,[34][35][36] Chlorogenic acid, rutin and ferulic acid had osteoprotective function by promoting bone mineral density. [37][38][39][40][41] Gallic acid in an in-vivo study showed positive effects around implants .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols decrease inflammatory mediators, such as histamine, and cytokines. Consequently decrease bone resorption 29,[34][35][36] Chlorogenic acid, rutin and ferulic acid had osteoprotective function by promoting bone mineral density. [37][38][39][40][41] Gallic acid in an in-vivo study showed positive effects around implants .…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41] Gallic acid in an in-vivo study showed positive effects around implants . 35 Catechin, green tea polyphenols also promotes osteogenesis .42 Syringic acid stimulates stem cells into osteoblasts, and it could be an osteogenic compound. 44 Cinnamic acid could be a part of osteogenic stimulant composite.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a sponge-like scaffold with different cross-linking chemistry was shown to induce osteogenesis of UMR106 osteoblasts in vitro and in vivo in calvarian defect as a result of EGCG action [ 207 ]. Gallic acid, another antioxidant, was incorporated in titanium substrate in order to deliver it for potential bone contact application [ 238 ]. The possibility to functionalize hydroxyapatite with Qu by different chemical syntheses for bone regeneration was explored in a triple co-culture model comprising MG63 osteoblast-like in contact with the biomaterial, osteoclast precursors 2T-110, and HUVECs [ 201 ].…”
Section: Towards Therapeutic Application: Antioxidant Biomaterialsmentioning
confidence: 99%
“…For the mineralization, various biomolecules have been used, including polyphenols, which have been successfully used for prevention and treatment of osteoporosis due to their protective effects on the bone mineral density [12,13]. In addition, polyphenols promoted biological mineralization of Ti6Al4V alloy by deposition of hydroxyapatite by mesenchymal stem cells cultured on this implant material, which is currently used in clinical practice [14]. In our earlier studies, polyphenols promoted mineralization of chitosan and gellan gum hydrogels (i.e., other materials that are promising for bone tissue engineering [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing prevalence of antibiotic-resistant bacteria, endowing biomaterials for implantation with antibacterial properties is desirable. Since gallotannins have shown antibacterial activity [14,26], they are expected to be promising antibacterial materials.…”
Section: Introductionmentioning
confidence: 99%